Better Quality of Sleep among Adolescents by Considering the Intensity of Social Media Utilization - Siti Habibah; Karina Megasari Winahyu; Hyang Wreksagung; Hera Hastuti; Kartini Kartini (Universitas Muhammadiyah Semarang, 2021)
The basic human needs, such as sleep quality, often take for granted that low sleep quality among adolescents could affect various health problems. One of the factors correlated with sleep quality in adolescents is the use of social media. This study aimed to identify the association between social media utilization and sleep quality among adolescents. The study used a descriptive correlation with a cross-sectional design. The Social Networking Time Use Scale and Pittsburgh Sleep Quality Index questionnaires were used based upon validity and reliability test. A Cross-sectional study was used with a convenience sampling frame by recruiting 188 adolescents. The analysis technique used was Chi-Square. The results showed that respondents with a high intensity of social media users who have good sleep quality were 29 (15, 4%) respondents, and those who have low sleep quality were 66 (35.1%) respondents. It revealed a significant association between the intensity of social media use and sleep quality in adolescents (X2 = 27,564a, df = 1, p< 0,05). It suggests that adolescents should reduce the intensity of social media use to improve their sleep quality.